Digital Transformation and Human Resource Development in the Industry 5.0 Era: A Sharia Economic Framework for Sustainable Organizational Innovation - Maguni, Wahyudin; Jajuli, M.Sulaeman; Sumiyadi, Sumiyadi; Gizachew Asresie, Gessesse; Haile Filatie, Tilahun (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Digital transformation in the Industry 5.0 era has generated a new paradigm in modern organizational management by positioning the integration of intelligent technologies and human-centered innovation as the primary foundation of organizational change. This article aims to examine the digital transformation of modern organizations from a Sharia economic perspective by emphasizing the implementation of maqāṣid al-sharīʿah principles in the development of a productive, sustainable, and human-centered industrial ecosystem. This study employs a library research method with a descriptive-analytical approach through a review of relevant literature on Industry 5.0, digital transformation, and Islamic economics. The findings indicate that the adoption of digital technologies, including Artificial Intelligence, big data, blockchain, and the Internet of Things, should be directed toward the realization of social welfare, distributive justice, transparency, and the prevention of exploitative practices. Human resource development constitutes a strategic factor through the enhancement of digital literacy, ethical competencies, and adaptive capabilities. Furthermore, challenges such as digital competency gaps, organizational cultural resistance, and weak Sharia-based technology governance can be addressed through the implementation of Sharia Digital Governance, the ethical optimization of intelligent technologies, the development of digital halal business models, and strengthened collaboration among academics, regulators, and industry practitioners. These practices imply that the Sharia economic perspective can serve as a guiding framework for digital transformation in the Industry 5.0 era, ensuring that technological innovation develops in a sustainable and equitable manner while generating long-term benefits for society.